Напрями вдосконалення загального трудового законодавства у сфері охорони праці працівників поліції - Бачинський, О. В.; Bachynskyi, O. V. (Юридична наука. - 2019. - № 11 (101), т. 2. - С. 329-335, 2019)
Визначено ключові проблеми у нормативно-правовому регулюванні охорони праці поліцейських. Здійснено критичний аналіз Концепції реформування системи управління охороною праці в Україні. Узагальнено наукові думки вчених щодо напрямів покращення загального трудового законодавства у цій сфері. Сформовано авторське бачення щодо напрямів вдосконалення загального трудового законодавства у сфері охорони праці працівників поліції.

The analysis of law enforcement practice makes it possible to ascertain the imperfection of the current legislation in the sphere of labor protection of employees of the bodies and divisions of the National Police of Ukraine. At the same time, in this context, it should be noted that we are talking about both general (which ensures the unity of legal regulation) labor legislation, the norms of which are aimed at regulating labor protection in all spheres of social life, and special legislation, which is directly aimed at labor protection employees of the National Police of Ukraine. Confirmation of the above is statistical data. Within the framework of this study, we will pay attention to the improvement of the general labor legislation, because it forms the basis of the implementation of activities in the relevant direction. The article, based on the analysis of scientific views of scientists and current legislation of Ukraine, identifies key issues in the legal regulation of police protection. A critical analysis of the Concept of labor protection management system reform in Ukraine has been carried out. The scientific opinions of scientists on the directions of improvement of the general labor legislation in this sphere are generalized. The author's vision on the directions of improvement of the general labor legislation in the field of labor protection of police officers is formed. It was concluded that in order to improve general labor legislation in the field of labor protection, it is generally necessary to develop and adopt two normative legal acts: 1) the new Law of Ukraine "On Labor Protection", because the normative legal act in force today is morally outdated and not takes into account: a) modern conditions and trends in the development of the labor sphere (the emergence of new forms of employment, the growing role of remote employment, etc.); b) the pandemic of the Corona virus infection (Covid-19); etc. 2) The strategy for the development of the labor protection system, which will take into account the socio-economic and political conditions of the modern development of society, and will also be aimed at the development of this institute within the framework of the implementation of labor activities by special subjects of labor law, for example, police officers.

Определены ключевые проблемы нормативно-правового регулирования охраны труда полицейских. Проведен критический анализ Концепции реформирования системы управления охраной труда в Украине. Обобщены научные мнения ученых относительно направлений улучшения общего трудового законодательства в этой сфере. Сформировано авторское видение направлений совершенствования общего трудового законодательства в сфере охраны труда работников полиции.
Directions for improving the general labor legislation in the field of labor protection of police officers
Бачинський, О. В. Напрями вдосконалення загального трудового законодавства у сфері охорони праці працівників поліції / Бачинський О. В. // Юридична наука. - 2019. - № 11 (101), т. 2. - С. 329-335.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; працівники поліції; police officers; работники полиции; охорона праці; labor protection; охрана труда; трудове законодавство; labor legislation; трудовое законодательство